2020
DOI: 10.1097/gme.0000000000001604
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Fennel seed powder on estradiol levels, menopausal symptoms, and sexual desire in postmenopausal women

Abstract: Objectives: The present study was designed to determine the effect of Fennel seed powder on menopausal symptoms, sexual desire, and serum estradiol levels in postmenopausal women. Methods: The present study was conducted on 80 eligible women (45-60 y) who were referred to the Mofatteh Gynecology Clinic in Yasuj, Iran. Participants were randomized into equal intervention and control (control) groups. The intervention and control groups received four caps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 29 publications
0
15
0
2
Order By: Relevance
“…Serum estradiol levels were measured at the beginning and at the end of the trial. The results of the study showed that menopausal symptoms were significantly (p < 0.05) reduced in the treatment group but there was no change in sexual desire 43 . In a triple-blind, placebo-controlled randomized trial involving 90 postmenopausal women aged 45 to 60 years 45 .…”
Section: Resultsmentioning
confidence: 84%
See 3 more Smart Citations
“…Serum estradiol levels were measured at the beginning and at the end of the trial. The results of the study showed that menopausal symptoms were significantly (p < 0.05) reduced in the treatment group but there was no change in sexual desire 43 . In a triple-blind, placebo-controlled randomized trial involving 90 postmenopausal women aged 45 to 60 years 45 .…”
Section: Resultsmentioning
confidence: 84%
“…Foeniculum vulgare Mill (Apiaceae) is an aromatic plant native to the Mediterranean region of Southern Europe, that was introduced into Mexico and is now cultivated across the Sierra Madre 40 . In MTM, fennel has been used traditionally for the management of dysmenorrhea and heavy menstrual bleeding, to increase breast milk, as well as an analgesic and anti-inflammatory to manage menopausal symptoms [41][42][43] . Traditionally, fennel has also been used for the treatment of respiratory disorders, indigestion, PMS, osteoporosis, cardiovascular disease, as well as to increase breastmilk production and libido 43 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is said to be effective for exerting estrogenic activity and lowering dysmenorrhea. The research of Ghaffari, et al [17] concluded that fennel seeds can significantly improve menopausal symptoms in postmenopausal women although their effects on estradiol levels and sexual desire are insignificant. This is reinforced by the research of Malakouti, et al, [15] showing that aromatherapy combination of lavender, fennel, geranium and rose shows a positive impact in improving sexual function without side effects in postmenopausal women.…”
Section: Introductionmentioning
confidence: 99%